Urbanism, Immigration and Housing. Public Policy in the City of Bologna. - Vaz, Arabela (International Planning History Society Proceedings, 2016)
Town planning’s social dimension is a feature of all aspects of modern cities, representing man and his need to be at the centre of the discipline and, as such, the relationship between housing, population growth and public policies. Faced with the phenomenon of immigration, the means available for city management cannot meet the needs of the social services sector in full, even though public policies have sought to bring it up to date, taking into account aspects that were previously considered of no importance to town planning such as those of an anthropological and sociological nature. The city of Bologna was not chosen randomly, but because it is emblematic of the rivalry between town planning and politics: from the country’s urban development, the reformist town planning proposed in the Sixties and Seventies and its social dimension to the difficult question of urban equity, property speculation, contrasts with national legislation and the importance of tools in solving the crucial problems of a city whose political, economic and social aspects have been continually altered and of late include a new component: the phenomenon of the immigration process that cannot be excluded from town planning. The complexity of the subject of housing and the concept of housing rights has always been acknowledged. This study, conducted in the field of town planning, arises from the need for a better understanding of international migration and its effect on the city and the relationship with town planning. Starting with a consideration of the economic crisis, I discuss the priorities and current requirements that the phenomenon of immigration represents and how the public policies adopted so far have tackled the issue of social equality for foreigners and Italians. The analysis of the main structural urban planning tools comprises what was the first city expansion plan (1889), the General Development Plan (PRG 85) and the Council Structural Plan, the new general urban planning tool for the city of Bologna that replaces the old PRG. The Council Structural Plan was adopted on 16/07/2007, approved on 14/07/2008 and came into force on 10/09/2008. The instruments studied in an integrated manner were the Council Operational Plan, approved on 04/05/2009 and effective since 03/06/2000, Urban Building Regulations, adopted on 20/04/2009 and effective since 20/05/2009, and Regional Act No. 20/2000. The research attempts to investigate the importance of democracy in public policies, specifying the instruments contained in urban development plans as important social planning tools, as the city is an area of conflict in which we find a series of interests that often conceal the fact that they do not correspond or correspond only partly with the aspirations of its inhabitants, without forgetting to analyse aspects such as social insecurity, diversity and urban integration, urban decay and regeneration, along with all their variables. The conclusion is that an area governed at a local level, but with a global outlook, has more probability of successfully implementing its policies, since transparency and disclosure of results to the public are vital.